Koranen som træningsprogram: Et case study af sura 18 - Mortensen, Mette Bjerregaard (Religionsvidenskabeligt Tidsskrift, 2016)
The article is a case study of a single narrative in the Qur’an’s sura 18. In this article, I explore and discuss the ethical dimensions of the Qur’anic world view. The article takes its point of departure in an outline of the pre-dominant eschatological strand in the Qur’an and different Qur’anic perceptions about reward and punishment. Then, I discuss the moral implications of the idea of divinely sanctioned deeds and actions as well as the existence of a Judgment Day. In light of this discussion, and based on an analysis of sura 18, I argue that Qur’anic piety can be seen as encompassing a particular ascetic ideal. Rather than dictating a radical secession from the world in terms of ascetic denial, the ascetic ideal authorizes participation in worldly life.